Modulation of Long Non-coding RNAs and MicroRNAs by Quercetin as a Potential Therapeutical Approach in Cancer: A Comprehensive Review - Asemi, Reza; Mafi, Ali; Sharifi, Mehran; Homayoonfal, Mina; Davoodvandi, Amirhossein; Asemi, Zatollah (Current Medicinal Chemistry, 2025)
Cancer can take years to develop, both at its beginning and during its development. All typical epithelial cancers have a long latency period, sometimes 20 years or more, and if they are clinically detected, distinct genes may include infinite mutations. Long non-coding RNAs (LncRNAs) are a subset of RNAs that regulate many biological processes, including RNA processing, epigenetic control, and signal transduction. Current studies show that lncRNAs, which are dysregulated in cancer, play a significant function in the growth and spread of the illness. LncRNAs have been connected to the overexpression of specific proteins that function in tumors' spread and growth. Moreover, through translational inhibition, microRNAs (miRNAs) regulates gene expression sequence specifically. Apart from that, non-coding RNAs known as miRNAs, with a length of around 22 nucleotides, controls gene expressions in a sequence-specific way either by preventing translation or degrading messenger RNA (mRNA). Quercetin appears to have a significant role in altering miRNA and lncRNA expression, which is linked to variations in the production of oncogenes, tumor suppressors, and proteins produced from cancer. Quercetin may change the earliest epigenetic modifications related to cancer prevention in addition to its usual antioxidant or anti-inflammatory effects. It would be beneficial to have more in-depth information on how Quercetin modulates miRNAs and lncRNAs to use it as a cancer therapeutic strategy. Here, we go through what is known about Quercetin's potential to modulate miRNAs and lncRNAs in various malignancies.
Keywords: colon cancer